2020
DOI: 10.1002/jlb.4ma0620-703rr
|View full text |Cite
|
Sign up to set email alerts
|

MXD1 regulates the H9N2 and H1N1 influenza A virus–induced chemokine expression and their replications in human macrophage

Abstract: Human infection with influenza A/Hong Kong/156/97 (H5N1) avian influenza virus is associated with a high mortality rate of 60%. This virus is originated from influenza A/Quail/Hong Kong/G1/97 (H9N2/G1) avian influenza virus. Since the 1990s, four lineages of H9N2 viruses have been circulating in poultry and cause occasional infection in humans in different countries. Due to its zoonotic and genetic reassortment potential, H9N2/G1 and H5N1 viruses are believed to be the next pandemic candidates. Previous report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Recently, Mamoor et al demonstrate the role of MXD1 in host cells’ response to COVID-19 infection [ 55 ]. Also, Howard et al reported the influence of MXD1 expression upon H1N1 and H9N2/G1 viral infection in the host [ 56 ]. Furthermore, silencing of MXD1 decreases the H9N2 replication process [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mamoor et al demonstrate the role of MXD1 in host cells’ response to COVID-19 infection [ 55 ]. Also, Howard et al reported the influence of MXD1 expression upon H1N1 and H9N2/G1 viral infection in the host [ 56 ]. Furthermore, silencing of MXD1 decreases the H9N2 replication process [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Howard et al reported the influence of MXD1 expression upon H1N1 and H9N2/G1 viral infection in the host [ 56 ]. Furthermore, silencing of MXD1 decreases the H9N2 replication process [ 56 ]. Similarly, PHF11 is one of the interferon-stimulated genes expressed by a host on viral infections that regulates cytokine genes in T lymphocytes [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…H5N1 and H9N2 are highly pathogenic. H9N2 induces CXCL10, RANTES, TNF-α, MIP-1α, and CCL2 expression ( 68 ). H5N1 induces TNF-α, CCL2, RANTES, CXCL10, IL-6, IL-8, and TGF-β3 ( 68 , 69 ).…”
Section: Macrophage Dysregulation In Viral Pathogenesismentioning
confidence: 99%
“…H9N2 induces CXCL10, RANTES, TNF-α, MIP-1α, and CCL2 expression ( 68 ). H5N1 induces TNF-α, CCL2, RANTES, CXCL10, IL-6, IL-8, and TGF-β3 ( 68 , 69 ). H7N9 induces heightened IL-6, TNF-α, and IL-8 expression ( 69 ).…”
Section: Macrophage Dysregulation In Viral Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation